2020
DOI: 10.3390/diagnostics10100830
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Methicillin-Resistant Staphylococcus aureus Directly from Blood for the Diagnosis of Bloodstream Infections: A Mini-Review

Abstract: Staphylococcus aureus represents a major human pathogen able to cause a number of infections, especially bloodstream infections (BSI). Clinical use of methicillin has led to the emergence of methicillin-resistant S. aureus (MRSA) and MRSA-BSI have been reported to be associated with high morbidity and mortality. Clinical diagnosis of BSI is based on the results from blood culture that, although considered the gold standard method, is time-consuming. For this reason, rapid diagnostic tests to identify the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Compared to previous reviews focusing on MRSA diagnostics [ 18 , 19 , 20 ], in this narrative review I found many studies reporting molecular methods moving towards POC diagnostics (but I recognize that this could be due to differences in a searching strategy or in the subjective selection of studies to report). However, all those studies are still at the proof-of-principle stage and need to be tested in a variety of isolates.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Compared to previous reviews focusing on MRSA diagnostics [ 18 , 19 , 20 ], in this narrative review I found many studies reporting molecular methods moving towards POC diagnostics (but I recognize that this could be due to differences in a searching strategy or in the subjective selection of studies to report). However, all those studies are still at the proof-of-principle stage and need to be tested in a variety of isolates.…”
Section: Discussionmentioning
confidence: 86%
“…Several other commercial molecular tests exist for the detection of resistance in S. aureus . For a description of those systems, please refer to these four reports [ 19 , 20 , 44 , 98 ].…”
Section: Molecular Methods For Antimicrobial Resistance Detection In S Aureusmentioning
confidence: 99%
See 1 more Smart Citation
“…MALDI-TOF MS is a proteomics-based soft ionization bio-mass spectrometry technique that is currently considered the best method for rapid identification of bacteria from different types of samples, such as blood, environmental or food samples. The three most common MALDI-TOF MS platforms are Bruker Microflex, Vitek MS and Autof MS 1000/2000 [ 141 ]. An important advantage of this method is the possibility of detecting bacterial isolates from biofilms.…”
Section: Testing Methods For Diagnosis Purposes Of Bacteria Involved ...mentioning
confidence: 99%
“…Several other systems that allow the rapid identification of different bacteria directly from clinical specimens are commercially available. These systems can be based on PCR methods (Biofire ® Filmarray ® , GeneDisc ® , BAX ® System, Cepheid Xpert ® , EntericBio real-time Gastro Panel I ® , FilmArray ® GI panel, Seeplex ® Diarrhea ACE Detection system and xTag ® Gastrointestinal Pathogen Panel, which is a FDA-approved and Health Canada-approved panel for the detection of multiple agents of gastroenteritis), nanoparticles-based technology (Verigene ® platforms, SeptiFast ® , SeptiTest ® ) or peptide nucleic acid fluorescent in situ hybridization (OpGen ® QuickFISH, Accelerate Pheno system) [ 20 , 21 , 22 , 23 , 24 , 117 , 141 ]. Recently, an automated T2Dx instrument platform (T2 Biosystems, Lexington, MD, USA) based on nuclear magnetic resonance technology has been developed that allows the multiplex detection of bacteria from the ESKAPE group in a single whole blood sample without a positive blood culture, in less than 6 h. The detection of bacterial pathogens in other infections, such as respiratory infections, gastroenteritis or sexually transmitted infections isbased on new NAAT technology coupled with different PCR types [ 156 , 157 ].…”
Section: Testing Methods For Diagnosis Purposes Of Bacteria Involved ...mentioning
confidence: 99%